Monitoring of glacier frontal parts on Galindez and Winter islands (the Argentine Islands) in 2018—2019 - Kh. I. Marusazh; V. M. Hlotov; Z. Siejka (Ukrainian Antarctic Journal, 2019)
The work presents an analysis of climate variability and glaciological changes of the Antarctic Peninsula and the results of glacier monitoring on Galindez Island and Winter Island (the Argentine Islands in the Wilhelm Archipelago, Antarctic Peninsula) in 2018—2019. The main objective of research was to determine how the volumes of glaciers changed in 2018—2019 in the course of a complex study. Methods. The material of the Ukrainian seasonal expedition of 2018—2019 was used: terrestrial laser scanning data of 2018, terrestrial digital photography of 2018 and 2019 and an unmanned aerial vehicle survey of 2019. The technique used to determine changes in the volumes of glaciers can significantly improve both the speed and accuracy of the measurements. It included complementary processing of scanning data and digital photography of 2018, and digital photography and aerial survey of 2019. Results. Changes in the volumes of glaciers were 36 000 m3 for the western part of the glacier on Galindez Island, 1 100 m3 for the southern part of the glacier on Galindez Island, and 9 800 m3 for the southern part of the glacier on Winter Island. Conclusions. The results demonstrate significant changes since 2002. This is confirmed quantitatively by independent studies of the West of the peninsula. Monitoring of the dynamics of glacier volumes enables detection of climatic and glaciological changes in the Antarctic region.